Designing a Game Board to Educate Children in Getting to Know the History of the Majapahit Kingdom - Dwidyanthi, Juwita Ayu (Jurnal Indonesia Sosial Sains, 2024)
This research aims to design a game board that attracts attention and is educational regarding the introduction to the history of the Majapahit kingdom, which includes the Majapahit kings and the stories of each king. An introduction to the history of the kingdom is a history lesson which is now a mandatory lesson. By studying the kingdom's history, it is hoped that children can understand historical values to form characters who love their homeland. I designed this game board to be an interactive medium as a fun lesson for children. The author designed an educational game board with interesting game components to increase interest and help children learn about the history and kings of the Majapahit kingdom. This game board was designed using a method based on the book 5 Phases of Design Graphic Process 4th. Edition by Robin Landa as follows: (1) Orientation. (2) Analysis and Strategy. (3) Conceptual Design. (4) Design Development. Lastly (5) Implementation. The result obtained in the assessment through a questionnaire that was tested at SD.N.067256 which is located on Jl.Paku.Tanah Six Hundred, kec.Medan Marelan and also for children un the author’s home environment, it can be concluded that more 85% of student and children respondents are interested in playing this educational board game as a medium for learning about the history of the Majapahit kingdom.